2008
DOI: 10.1523/jneurosci.1618-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

d-Aspartate Prevents Corticostriatal Long-Term Depression and Attenuates Schizophrenia-Like Symptoms Induced by Amphetamine and MK-801

Abstract: IntroductionSchizophrenia (SCZ) is a severe mental disorder afflicting ϳ1% of the population worldwide. Despite decades of intensive research, the precise etiology of this devastating mental illness remains, so far, an unresolved puzzle (Sawa and Snyder, 2002). It has been proposed that dysfunction of dopaminergic neurotransmission occurs in SCZ patients (Snyder, 1976); however, a large body of evidence recently proposed that abnormal serotonergic and glutamatergic neurotransmission might also be implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
115
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 52 publications
7
115
0
Order By: Relevance
“…Indeed, DDO-deficient mice have elevated concentrations of D-Asp in several brain regions and exhibit specific antidepressant and antischizophrenic behaviors. 26,27) These findings support the concept that DDO inhibitors that activate NMDA receptor function by augmenting the levels of D-Asp in the brain would be new and useful antipsychotic drugs for the treatment of NMDA receptor-related diseases. DDO inhibitors may also be lead compounds for the development of new drugs to treat infertility since D-Asp is thought to be involved in the quality control of germ cells.…”
supporting
confidence: 59%
“…Indeed, DDO-deficient mice have elevated concentrations of D-Asp in several brain regions and exhibit specific antidepressant and antischizophrenic behaviors. 26,27) These findings support the concept that DDO inhibitors that activate NMDA receptor function by augmenting the levels of D-Asp in the brain would be new and useful antipsychotic drugs for the treatment of NMDA receptor-related diseases. DDO inhibitors may also be lead compounds for the development of new drugs to treat infertility since D-Asp is thought to be involved in the quality control of germ cells.…”
supporting
confidence: 59%
“…Other studies using mutagenesis and homology modeling of GluN2A and GluN2B LBDs have suggested that NMDA cannot bind to GluA subunits because of steric clash between the N-methyl group of NMDA and Met708 in GluA2, which is conserved among all AMPA receptors (Laube et al, 2004;. GluN2 endogenous agonists include glutamate, D-and L-aspartate (Benveniste, 1989;Nicholls, 1989;Fleck et al, 1993;Schell et al, 1997;Wang and Nadler, 2007;Errico et al, 2008;Zhang and Nadler, 2009), homocysteate, and cysteinesulfinate (Do et al, 1986(Do et al, , 1988Olney et al, 1987;Yuzaki and Connor, 1999) (Table 8). Cyclic analogs with conformationally constrained rings also act as potent GluN2 agonists, in some cases with EC 50 values lower than glutamate (Shinozaki et al, 1989;Schoepp et al, 1991;Erreger et al, 2007) (Table 8).…”
Section: Glutamate Receptor Ion Channelsmentioning
confidence: 99%
“…The majority of evidence gathered so far would suggest that D-Asp is a ligand for NMDARs (Kiskin et al 1990;Olverman et al 1988). Errico et al (2008aErrico et al ( , 2008bin press) found that D-Asp activated currents via NR2A-D receptor subunits and increased long-term potentiation through NMDAR activity, yet it also activated currents independently of NMDARs, suggesting a unique D-Asp receptor. Meanwhile, Huang et al (2005) found that D-Asp did not activate AMPA/ kainate or metabotropic glutamate receptors.…”
mentioning
confidence: 99%